PENERAPAN KONSUMSI JUS BUAH KURMA (PHOENIX DACTILIFERA) TERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS RANTAU PANJANG KIRI KABUPATEN ROKAN HILIR - Wati, Rusna; Aifa, Wira Ekdeni; Ruspita, Rika; Rahmita, Hirza (Ensiklopedia of Journal, 2025)
Anemia is a condition in which the level of hemoglobin (Hb) in the body is below normal according to certain groups of people. Based on data obtained from the Sinama Grand Health Center, where the incidence of anemia in pregnant women in 2020 was recorded 29 cases with a target of 581 pregnant women, while in 2021 the incidence of anemia has increased to 31 cases with a target of 532 pregnant women. The research objective was to determine the effectiveness of consumption of date palm juice (phoenix dactilifera) on increasing HB levels in third trimester pregnant women at the Sinama Grand Health Center. This type of research is quantitative and quasi-experimental design with one group pretest-posttest. The population is pregnant women and a sample of 12 people, with Total Sampling. The research instruments were observation sheets, pathographs and date juice. Data analysis using univariate and bivariate. The univariate results showed that pregnant women in the third trimester before being given date palm juice experienced anemia with HB levels in the moderate anemia category, namely 100% and after being given date juice, HB levels showed no anemia, namely 91.7%. The results of the Wilcoxon test showed the effectiveness of date palm juice on increasing HB levels in pregnant women, with a p-value of 0.000 <0.05. It is hoped that the Sinama Grand Health Center can improve services, especially in the field of care for pregnant women to increase HB levels for pregnant women.Keywords: Dates Juice, Anemia, Pregnant Women